Modelling of Sustainable Development - YEMELINA, Natalya; OMAROVA, Ainura; ANARA, Kurmanalina (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).15, 2018)
Annotation. In the article, the authors first proposed a comprehensive model for assessing and predicting the indicators of sustainable socio-ecological and economic development of the Republic of Kazakhstan. These aspects are system forming in the activities of any state in the development of programs and strategic documents. The main objective of which is to ensure the social well-being of the population, which is impossible without economic development and ensuring the reproduction, process as well as maintaining environmental standards. Based on the correlation-regression analysis a system of econometric equations describing the relationship of the main indicators of the development of the economic, social and environmental spheres and various factors, respectively, explaining the changes in these spheres had compiled.